Postprandial Hyperglycemia as a Significant Risk Factor for Coronary Heart Disease - Al-Lehibi, Khalid I.; Al-Lehibi, Khalid I.; Hussein, Mousa Q.; Al-Hergani, Zaidan K. (AL-Kindy College Medical Journal, 2011)
Background: The highest concentrations of blood glucose during the day are usually found postprandialy. Postprandial hyperglycemia (PPH) is likely to promote or aggravate fasting hyperglycemia. Evidence in recent years suggests that PPH may play an important role in functional & structural disturbances in different body organs particularly the cardiovascular system. Objective: To evaluate the effect of (PPH) as a risk factor for coronary Heart disease in Type 2 diabetic patients. Methods: Sixty-three type2 diabetic patients were included in this study. All have controlled fasting blood glucose, with HbA1c correlation. They were all followed for five months period (from May to October 2008). A two hour postprandial glucose (PPG) was done for all. Other risk factors were taken in consideration such as hypertension, obesity, and dyslipidemia. The study was performed on those patients after at least three months of controlled fasting blood glucose. ECG was done to all of them. Results : Out of the 63 type 2 diabetic patients, 20 had normal PPG and HbA1c levels, one of them (5%), has ischemic changes on ECG twenty patients had normal HbA1c & High PPG with 7 (35%) of them showed ischemic changes on ECG 17 patients showed a high PPG and a high HbA1c with four of them showed ischemic changes on ECG P<0.05. The remaining 6 patients had normal PPG but high HbA1c & also only one of them showed ischemic changes on ECG. Conclusion This study showed that PPH is a significant risk factor for ischemic heart disease (IHD).